DEMOCRATIC PROGRESSIVE PARTY’S DIGITAL POPULISM TOWARDS REUNIFICATION NARRATIVES IN X 2020-2024 - Yanuariandi, Muhamad Alfi; Jatmika, Sidik (Universitas Padjadjaran, 2025)
This research aims to analyze how the Democratic Progressive Party (DPP) utilizes digital populism on platform X (formerly Twitter) to reinforce Taiwan's distinct identity and shape public opinion regarding Taiwan-China reunification. A mixed-methods approach was employed, analyzing 920 posts from 2020 to 2024. Data were examined using Naïve Bayes classification for quantitative sentiment analysis and qualitative thematic evaluation grounded in Social Identity Theory. The research results reveal three primary findings. First, the DPP successfully establishes an